Percepción y conocimiento popular sobre los cocodrilos en el “Área de Protección de Flora y Fauna Manglares de Nichupté”, Quintana Roo, México - Cornejo, Alejandra; Gómez-Hernández, Yadira; Gómez-Álvarez, Graciela; González-Rebeles, Carlos; Ulloa-Arvízu, Raúl; Villegas, Alejandro (Instituto de Ecología, A.C., 2021)
The success of crocodile conservation programs highly depends on local people’s views, perceptions, and knowledge regarding these reptiles. The present study assessed these variables across the Nichupté lagoon through semi-structured interviews. Answers were grouped into three categories: thoughts regarding the presence of crocodiles in the area, locals’ perception on crocodiles, and local knowledge on crocodiles. Most of the 221 people interviewed showed no aversion to crocodiles, 93.2% knew about the presence of crocodiles in the lagoon, and 98.1% mentioned that it is essential to conserve these reptiles. On the other hand, 77.5% (men) and 70.5% (women) agreed that “it is fine” to share the lagoon with crocodiles. Concerning people’s perceptions about crocodiles, “Quiet”, “Indispensable” and “Interesting” were the most frequent answers. Regarding the local knowledge, we found a positive, statistically significant correlation between this variable and education, with those having high school degrees mentioning "Habitat" and those with college degrees mentioning "Reptile" more frequently. Conservation policies should be redesigned to include continuous environmental education programs that promote positive attitudes towards crocodile species. They should also include measures to guarantee the dissemination of necessary information to protect human and crocodile lives, is essential to consolidate conservation programs.